Study on Morphological, Microbiological and Qualitative Chemical Composition of Gnetum leptostachyum var. elongatum Markgr. Collected at Bach Ma National Park - Thua Thien Hue - Thang, Nguyen Van; Thu Hang, Nguyen; Thi Thanh Huyen, Chu; Van Truong, Bui; Tran Mai Phuong, Nguyen; Trong Hoang Ngan, Nguyen; Quoc Dai, Hoang; Thi Xuan, Nguyen; Minh Tuan, Tran; Thi Thu Hang, Nguyen; Thi Van, Dinh; Thanh Binh, Vu; et al. (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2025)
Gnetum leptostachyum var. elongatum Markgr. is a species of the Gnetaceae family collected at Bach Ma National Park – Hue city. The database system from plant characteristics to the chemical composition of Gnetum leptostachyum var. elongatum Markgr. species will be the premise for future studies. Fresh samples were collected for morphology and anatomical structure assessment. Plant powders and chemical compounds were also investigated and characterized. The results showed that many secondary metabolic products, such as calcium oxalate, essential oil, resin, and starch, were found in the anatomical structure and medicinal powder of this species. The study identified 14 chemical compounds, including alkaloids, flavonoids, saponins, anthranoids, coumarins, cardiac glycosides, tannins, organic acids, reducing sugars, carotenoids, sterols, amino acids, essential oils, and polysaccharides. These data show the potential and medicinal significance of Gnetum leptostachyum var. elongatum Markgr. species in the medical area.